Indirect Adaptive Type-2 Fuzzy Impulsive Control of Nonlinear Systems - Li, Yimin; Sun, Yuanyuan; Hua, Jing; Li, Li (IEEE transactions on fuzzy systems, 2015)
In this paper, a novel indirect adaptive interval type-2 fuzzy tracking control is proposed. Strategy with impulsive and Lyapunov synthesis approach, it handles the training data corrupted by noise or rule uncertainties for linear and nonlinear systems involving external disturbances. In comparison with conventional methods, the advocated approach guarantees closed-loop stability. The output tracking error of the overall system will converge to zero asymptotically by the generalized Barbalat's lemma. Numerical simulations are given to illustrate the effectiveness of the proposed techniques.